Pencegahan Stunting Pada Anak Dalam Persepektif Islam Di Kota Bandar Lampung - Rumadani Sagala; Anas Malik; Muhamad Bisri Mustofa (AKM, 2023)
Stunting is a major problem in the growth and development of children. The problem of stunting is always synonymous with health problems in children. In fact, parenting patterns by parents who are not correct can cause stunting in children. The purpose of this service is to provide understanding to the community in preventing stunting in the Islamic religious approach. The research approach used in this study is the PAR or Participatory Action Research method. Participatory Action Research is a research model that seeks something to link the research process into the process of social change. The result of the service is an increase in public understanding. Participants in mentoring activities at the taklim assembly and health activities can provide further education to families and the community regarding stunting prevention. Most posyandu cadres have started implementing Islamic life in their routine activities. The socialization from posyandu cadres was in line with the material obtained from the socialization of Islamic healthy living which had been held previously.